Reproductive Success and Broad Survival of Bobwhite Quail as Affected by Grazing Practices - Ruben Cantu; Daniel D. Everett (National Quail Symposium Proceedings, 2017)
A radio telemetry study of 76 nesting and brood rearing bobwhite quail (Colinus virginianus texanus) hens was conducted during 1980 and 1981. Four study sites with different habitats and cattle grazing intensities were used. The 1980 breeding season was hot and draughty. Nine nests were found and three clutches of eggs hatched. There was a 1:3 adult to juvenile ratio in fall shot birds, and 66 percent hatched after 1 September following the rains of Hurricane Allen on 9 August. The 1981 breeding season was wet with average temperatures. One nest was found and seven broods were known to have hatched . Examination of quail wings showed a 1:5 adult to juvenile ratio, with 69 percent of the juvenile birds hatched prior to July 16, 9 percent in the latter half of July, 10 percent in August, 9 percent in September, and 2 percent in October. Seven unsuccessful nests were found. Five were destroyed by predators and two were abandoned. Chick mortality was 49 percent within the first two weeks of life in nine broods. Thirty-eight of 76 radio tagged hens were killed during the reproductive seasons. Reproductive success was highest during the wetter breeding season and highest in pastures that were moderately grazed and in good range condition.